Saúde Indígena em perspectiva : explorando suas matrizes históricas e ideológicas - Teixeira, Carla Costa; Garnelo, Luiza (Coleção Saúde dos povos indígenas., 2014)
Understanding the current public policy on Indigenous health in the light of its background: with this objective, researchers from different specialties and regions of the country came together to produce this collection, which seeks to increase the visibility of Indigenous voices in the Brazilian sociopolitical scenario. The chapters offer a very consistent overview of the field of indigenous health in Brazil. The book analyzes the political and institutional context that gave rise to the SUS and, particularly, the Indigenous Health Subsystem. It points out the differences and difficulties, but also points out possible ways of articulating the official medical system and the Indigenous system. More: it corroborates the importance of dialogue to establish creative interactions and, above all, "contribute to the provision of culturally sensitive health care".